La impronta de Verde Memoria en la poesía castellana de J. R. Wilcock (El Hilo de la Fabula, 2018)
In this article, we have considered the connections between the literary journal Verde Memoria (1942–1944) and the language of the Spanish poetry of Juan Rodolfo Wilcock. Firstly, we have analyzed the selection and the criticism of the local Argentinian poetry during the 40 and 50 decades. Secondly, we have described the translation from the ideological and aesthetic perspective of the journal. Finally, we have concluded emphasizing the relevance of Verde Memoria regarding the Spanish texts of Wilcock.
Keywords: Verde Memoria; Literary Journals; Neo–romantic Poetry; J.R. Wilcock; Translation